Contrasting Comprehension of HIV Research by Adolescents, Young Adults, and Caregivers in Western Kenya: A Cross-sectional Analysis. (14th September 2022) - Dyer, Jessica; Shah, Seema K.; Agot, Kawango; Wilson, Kate; Bosire, Risper; Badia, Jacinta; Inwani, Irene; Beima-Sofie, Kristin; Richardson, Barbra A.; John-Stewart, Grace; Kohler, Pamela
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Adolescent participation in research is critical to inform interventions that improve outcomes for this group. Adolescents and young adults living with HIV often present to care without caregivers, yet caregiver permission is typically required for those younger than 18 years. We evaluated whether understanding of key consent information differed between adolescents ( n = 1, 393) and caregiver adults ( n = 169). Compared with caregivers, adolescents aged 10–14 years showed significantly lower understanding, whereas understanding for older adults living with HIV did not differ significantly from caregivers. Risks were the least understood consent information for all age groups. Our findings suggest that for low-risk research, waiving caregiver permission requirements will not compromise the ethical need to ensure understanding of research before enrollment and may allow adolescents greater access to potential research benefits.